Use of the Analytic Hierarchy Process Method in the Variety Selection Process for Sugarcane Planting - Schiavon, Luiza L. P. [UNESP]; Lima, Pedro A. B. [UNESP]; Crepaldi, Antonio F. [UNESP]; Mariano, Enzo B. [UNESP] (MDPI, 2023)
The sugar and alcohol sectors are dynamic as a result of climate alterations, the introduction of sugarcane varieties, and new technologies. Despite these factors, Brazil stands out as the main producer of sugarcane worldwide, being responsible for 45% of the production of fuel ethanol. Several varieties of sugarcane have been developed in the past few years to improve features of the plant. This, however, led to the challenge of which variety producers should choose to plant on their property. In order to support this process, this research aims to test the application of the analytic hierarchy process (AHP) method to support producers to select which sugarcane variety to plant on their property. To achieve this goal, the research relied on a single case study performed on a rural property located inland of São Paulo state, the main producer state in Brazil. The results demonstrate the feasibility of the approach used, specifically owing to the adaptability capacity of the AHP method.